Have the Mountains Fallen? : Two Journeys of Loss and Redemption in the Cold War - Lilley, Jeffrey (Book collections on Project MUSE., 2018)
After surviving the blitzkrieg of World War II and escaping from two Nazi prison camps, Soviet soldier Azamat Altay was banished as a traitor from his native home land. Chinghiz Aitmatov became a hero of Kyrgyzstan, writing novels about the lives of everyday Soviet citizens but mourning a mystery that might never be solved. While both came from small villages in the beautiful mountainous countryside, they found themselves caught on opposite sides of the Cold War struggle between world superpowers. Altay became the voice of democracy on Radio Liberty, while Aitmatov rose through the ranks of Soviet politics. Yet just as they seemed to be pulled apart in the political turmoil, they found their lives intersecting in moving and surprising ways. Have the Mountains Fallen? traces the lives of these two men as they confronted the full threat and legacy of the Soviet empire. Through personal and intersecting narratives of loss, love, and longing for a homeland forever changed, a clearer picture emerges of the experience of the Cold War from the other side.